2022
DOI: 10.9734/ejmp/2022/v33i630471
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Pharmacological and Therapeutic Potential of Aloe barbadensis Miller

Abstract: Aloe vera, a popular succulent perennial medicinal plant with a wide range of phytochemicals that have shown various pharmacological activities including anti-oxidant, antimicrobial, antidiabetic, wound healing promotion and so on. Acemannan, aloe-emodin, aloin, aloesin, and emodin are widely investigated active constituents that show various pharmacological activities. Thus, the purpose of this review is to highlight previous pharmacological studied conducted in vivo, in vitro and human assays over the past d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…Aloe vera gel is known to exert anti-inflammatory, antibacterial, antioxidant, immune-stimulating and hypoglycemic characteristics, along with a range of other pharmacological effects [20,21]. Fani and Kohanteb [22] (2012), reported that aloe vera gel can exhibit a significant bactericidal effect against cariogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Aloe vera gel is known to exert anti-inflammatory, antibacterial, antioxidant, immune-stimulating and hypoglycemic characteristics, along with a range of other pharmacological effects [20,21]. Fani and Kohanteb [22] (2012), reported that aloe vera gel can exhibit a significant bactericidal effect against cariogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%